Building a healthy-wealthy society with reference to 'Rich Dad, Poor Dad' / Che Asniza Osman and Jahjaiton Arsad - Osman, Che Asniza; Arsad, Jahjaiton (2006)
'Rich Dad, Poor Dad' (RDPD) written by Robert Kiyosaki and Sharon L. Lechter has stories that make sense and disseminates invaluable messages especially in teaching people on how to be millionaires. If western commentators recommend this book as providing information on enriching wisdom of staying rich, the writers on the other hand, are more interested in digging out some values that could be considered and practised by all. However, the concern here is to focus only on the Malay society. This article provides some wake-up calls to the Malays, to move forward with passion and responsibility to build a healthy-wealthy race in order to strengthen the economic wealth for the religion and country. Only certain points were extracted from RDPD. Nevertheless, it is hoped that readers would be continuously inspired to expand their knowledge on financial freedom after reading this article.